ANALISIS STRATEGI PIVOT PADA START-UP DIGITAL DALAM MENGHADAPI KETIDAKPASTIAN PASAR - Zahra, Siti; Salsabila, Salsabila; Agistin, Silvi; Nur Rahman, Muhammad Zahran (Jurnal Inspirasi Ilmu Manajemen, 2025)
Digital start-ups significantly contribute to economic growth; nonetheless, they encounter a substantial failure rate due to their incapacity to adjust to market realities. Market uncertainties, including evolving customer tastes and intense competition, necessitate the adaptation of plans for business models, products, or target markets. Extensive research has been conducted on market uncertainty; yet, the development of pivot strategies as a response remains limited. This study seeks to examine the pivot methods employed by digital start-ups in response to market uncertainty. This research employs a qualitative methodology utilizing a case study approach. The data was acquired through comprehensive interviews with founders and start-up executives who have pivoted, along with the examination of documents like business reports and academic publications. The data analysis employed a theme method, encompassing steps of data reduction, presentation, and conclusion formulation. Triangulation is employed to enhance the validity of the results. The study's results indicate that the pivot strategy is implemented by modifications in products, business strategies, and technology. Start-ups that effectively execute pivots typically embrace data- and technology-driven tactics. Nonetheless, obstacles like as timing of pivots, internal opposition, and resource constraints frequently impede the execution of this plan. The pivot strategy is essential for the viability of digital start-ups in a volatile industry. The effectiveness of the pivot relies on the ability to analyze market trends and guarantee a planned and scalable execution.